Personalized medicine: biomarkers and companion diagnostics - Bernardini, Renato; Gancitano, Giovanni; Balice, Angela; Di Mauro, Rosaria; Cantarella, Giuseppina; Dionisi, Matteo (Farmeconomia. Health Economics and Therapeutic Pathways, 2018)
Great expectations are bound to the current evolution of medicine to personalized medicine. Thanks to rapid advances in genomics and molecular biology, new markers can be revealed for the presence of or susceptibility to a disease, or response to treatment. On such markers, diagnostic tests can be based; companion diagnostics (CDx, often called In Vitro devices) are diagnostic tests “coupled” with a therapeutic drug, aimed at assessing its applicability to a specific class of patients. As well as exemplifying some already implemented CDx applications, the purpose of this article is to highlight potentials and problems of personalized medicine today. In particular, the opportunity is analyzed for the co-development of a new drug and its CDx, through a parallel base research. This approach is promoted by the regulatory agencies but, due to scientific and economic factors implicit in the process, it is taking-off slowly. Personalized medicine deserves to grow and to expand, first of all because it simultaneously promises to substantially improve patient care and to make big costs savings for healthcare systems. From this point of view, all stakeholders (diagnostics manufacturers, clinical testing laboratories, pharmaceutical firms, the Department of health, and other bodies) should talk to each other in order to support the advancement of personalized medicine.